2013
DOI: 10.1002/lsm.22140
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Therapeutic Class IV (10 W) Laser Treatment for Epicondylitis

Abstract: These findings suggest that laser therapy using the 10 W class IV instrument is efficacious for the long-term relief of the symptoms associated with chronic epicondylitis. The potential for a rapidly administered, safe and effective treatment warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
0
38
0
1
Order By: Relevance
“…Many previous researchers conducted their studies on low level laser application with a wavelength of 904 nm and dosage between 2.3 and 4 J/cm 2 [17]. In the present study, the applied wavelength was 980 nm with a dosage of 10 J/cm 2 that increases the level of penetration and energy absorbed density and better effectiveness for laser application.…”
Section: Modern Rehabilitationmentioning
confidence: 83%
See 3 more Smart Citations
“…Many previous researchers conducted their studies on low level laser application with a wavelength of 904 nm and dosage between 2.3 and 4 J/cm 2 [17]. In the present study, the applied wavelength was 980 nm with a dosage of 10 J/cm 2 that increases the level of penetration and energy absorbed density and better effectiveness for laser application.…”
Section: Modern Rehabilitationmentioning
confidence: 83%
“…Oken et al reported that low level laser with short-term application had no effect in improving pain since the absorbed energy density was not enough, while long-term irradiation would be much more effective on pain reduction or better grip strength [17]. Based on laser theory, effectiveness of laser irradiation depends on the amount of absorbed energy [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A seemingly reasonable dose may just be the effect of a thin fiber, 2 and a high energy may be dispersed over a large area, thus resulting in a low dose. 3 Qualified readers of an article may be able to calculate what is missing if other parameters such as the spot size (cm 2 ) is reported. However, anyone should be able to have access to all the necessary Tables 1-3 show the work of some fictional authors, Smith et al, who use the tabular method to include necessary detail for their treatment of carpal tunnel syndrome.…”
mentioning
confidence: 99%